Combination therapy and rehabilitation in patients with breast diseases concurrent with cervical dysplasia - I. P. Aminodova; N. P. Lapochkina (ABV-press, 2015)
The breasts have been assessed in women with pre-invasive diseases of the cervix uteri in the presence of human papillomavirus infection. Thepaper describes a comprehensive approach to treating benign breast diseases and pre-invasive cervical ones with the multitargeted agentPromisan that is able to improve the breasts and cervix uteri.